1992
DOI: 10.1042/bj2860361
|View full text |Cite
|
Sign up to set email alerts
|

E.p.r. and magnetic circular dichroism spectroscopic characterization of bacterioferritin from Pseudomonas aeruginosa and Azotobacter vinelandii

Abstract: The e.p.r. and magnetic circular dichroism (m.c.d.) spectra of bacterioferritin (BFR) extracted from Pseudomonas aeruginosa and Azotobacter vinelandii have been studied over a wide temperature range down to liquid-helium temperature. The e.p.r. spectra show the presence of low-spin Fe3+ haem with g values of 2.86, 2.32, 1.48 (P. aeruginosa) and 2.88, 2.31, 1.46 (A. vinelandii), in both the presence and absence of the BFR core. Together with evidence from the porphyrin-to-Fe3+ charge-transfer band at 2240 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
1

Year Published

1993
1993
2006
2006

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 25 publications
2
27
1
Order By: Relevance
“…Bacterioferritins differ from mammalian ferritins in that they have up to 12 noncovalently bound heme groups (4,39). The heme centers have bis-methionine ligation (12,13). Dps proteins have not been as thoroughly characterized as ferritins or bacterioferritins yet.…”
mentioning
confidence: 99%
“…Bacterioferritins differ from mammalian ferritins in that they have up to 12 noncovalently bound heme groups (4,39). The heme centers have bis-methionine ligation (12,13). Dps proteins have not been as thoroughly characterized as ferritins or bacterioferritins yet.…”
mentioning
confidence: 99%
“…Furthermore, bacterioferritins differ from ferritins in possessing heme b prosthetic groups (up to 12 groups/24 subunits), which have a very low redox potential that depends on the presence (Ϫ475 mV) or absence (Ϫ225 mV) of an iron core (Watt et al, 1986). Magnetic circular dichroism (MCD), electron-paramagnetic resonance (EPR) spectroscopy, extended x-ray absorption fine structure, and x-ray crystallographic studies have shown that the heme iron of the bacterioferritins has a unique bis-methionine ligation (Cheesman et al, 1990(Cheesman et al, , 1992George et al, 1993;Frolow et al, 1994). Modeling studies suggested that the E. coli BFR possesses two potential heme-binding sites (site I and site II), each containing a pair of methionine residues correctly disposed to bind heme (Cheesman et al, 1993).…”
mentioning
confidence: 99%
“…Secondly, the cytochrome contains both haem and non-haem iron. Thirdly, the cytochrome contains protophorphyrin 1X coordinated by two methionine residues, so far a unique feature of bacterioferritins [45]. Fourthly, the first ten amino acids of the N-terminal sequence of its subunits show 70% sequence identity to bacterioferritin subunits from other bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…1), characteristic of bis-methionine ligation of the haem [45]. Cytochrome b,,, was further analysed by PAGE and SDS/PAGE (data not shown).…”
Section: Cytochrome B Isolated From R Cupsulutus 37b4 Is a Bactermentioning
confidence: 99%